2021
DOI: 10.3390/min11111189
|View full text |Cite
|
Sign up to set email alerts
|

Modified Red Muds and Slag Based Hydraulic Binders for Zn Removal: A Matrix-Spiking Approach Applied on Clayey Sediments

Abstract: Dredging sediments can be implemented as primary resources in several civil engineering applications, on the condition that the release of anthropogenic compounds meets environmental requirements. The remediation of sedimentary wastes constitutes therefore, a key step before valorization consideration in circular economy schemes. This study focused on Zn removal from clayey river sediments dredged in northern France (Lille, Saint-Omer and Aire-Sur-La Lys) using a Thermo-Evolved Red Mud (TERM) and a Slag Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(84 reference statements)
1
0
1
Order By: Relevance
“…The closeness of these two values suggested a buffering effect of FCS 750 instead of a significant influence of the initial pH on the uptake process. Contrary to this observation, several studies suggested an increase of Zn stabilization at pH = 7 as a response to growing alkalinity [51]. This was not observed here, probably due to the impact of FCS 750 on the acido-basic configuration of the medium during the blending steps.…”
Section: Adsorption Capacitycontrasting
confidence: 99%
See 1 more Smart Citation
“…The closeness of these two values suggested a buffering effect of FCS 750 instead of a significant influence of the initial pH on the uptake process. Contrary to this observation, several studies suggested an increase of Zn stabilization at pH = 7 as a response to growing alkalinity [51]. This was not observed here, probably due to the impact of FCS 750 on the acido-basic configuration of the medium during the blending steps.…”
Section: Adsorption Capacitycontrasting
confidence: 99%
“…To evaluate the stabilizing capacity of FCS 750 on polluted solid matrices, three different fluvial sediments (La Deule, Aa and La Lys) were spiked with Zn solutions before treatment. The mechanisms of Zn-trapping and its promoting factors are described in a previous study [51]. This study indicated that the Aa sediments had the best Zn retention properties because of a higher alkalizing capacity.…”
Section: Fcs 750 Application On Spiked Solid Matricessupporting
confidence: 51%